Peran Sumber Daya Manusia dan Strategi Meminimalkan Risiko untuk Meningkatkan Kinerja Perusahaan - Wahyu Yuda Pradana; Arba Sunur; Bima Andika; M Farid Abrar; Arsyadona Arsyadona (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Companies engaged in the field of service providers or production of goods have the same goal, namely to make a profit, in addition to making a profit, every company certainly wants to provide products or services that can provide satisfaction to each of its customers by including risk management in it. Risk management can be interpreted as a method used by companies to find out, monitor, and control the risks that will arise from business activities. Risk management seeks to improve company performance. In risk management in minimizing company problems, it needs to be carried out by a company leader such as identifying, measuring, and handling a company risk. The purpose of this study is to provide a strategy to improve company performance by preparing good human resources and minimizing the risks that exist in a company.